Neurodevelopment in the first year of children exposed to SARS-CoV-2 during intrauterine period: systematic review - Aline Helena Nascimento Veloso; Aurélio de Melo Barbosa; Maysa Ferreira Martins Ribeiro; Flávia Martins Gervásio (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To identify, in the literature, the implications of gestational exposure to SARS-CoV-2 on neurodevelopment in the first postnatal year, focusing on changes in the motor, personal-social, socio-emotional, and communication and language domains. Method: Systematic review with narrative synthesis, considering neurodevelopmental outcomes, categorized according to gross and fine motor skills, personal-social interaction, socio-emotional aspects, and communication and language. Searches were conducted in PubMed, LILACS/BIREME, and EMBASE databases between January 2020 and June 2023. Two independent researchers performed selection by reading the title and abstract and applying the inclusion and exclusion criteria. Cohort studies that evaluated children up to one year old, exposed to SARS-CoV-2 in utero, were included. The Newcastle-Ottawa scale was used to assess methodological quality. Results: Seventeen articles were included, with methodological quality ranging from intermediate to good. The most frequently used instrument to characterize neurodevelopment was the Ages & Stages Questionnaires. Infants aged 0 to 3 months had lower scores for fine and gross motor skills. Infants aged 3 to 12 months had more fine motor, social and communication and language impairments. Conclusion: Most infants exposed to SARS-CoV-2 showed development as expected, however delays were identified in the motor, personal-social, socio-emotional and communication and language domains according to the age group.